Neoliberalism, Agriculture and Farmer Stories: Voices of Farmers from the Margins of India. (July 2015) - Rastogi, Rahul; Dutta, Mohan J.
Agriculture in India is in a state of crisis. Policy changes adopted by the Indian government in the last two decades seek to commercialize agriculture and integrate domestic agriculture into the world markets. These changes brought about by the Indian government follow a neoliberal impetus. As a result, farmers in India are facing novel situations that have given rise to problems at multiple levels. This study seeks to understand sense-making of agriculture and problems related to it, as engaged in by the farmers of rural Uttar Pradesh (India). The study situates the meaning of agriculture as articulated by farmers within the culture–structure–agency matrix.